2016
DOI: 10.1111/sed.12261
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentological perspectives on climatic, atmospheric and environmental change in the Neoproterozoic Era

Abstract: Sedimentological insights underpin many of the important recent advances in understanding of Earth system behaviour in the Neoproterozoic Era. This article reviews three main areas: (i) chemical proxies and their preservation, with emphasis on carbonate facies; (ii) glacial and post-glacial facies, including their age constraints; (iii) sedimentary evidence for biotic innovations and responses. Chemostratigraphy plays an important role in ordering Neoproterozoic events and defining disturbances to the carbon c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 375 publications
(593 reference statements)
2
56
0
Order By: Relevance
“…Available evidence suggests anoxic oceans (largely ferruginous but locally euxinic) beneath an oxygenated surface mixed layer (Och & Shields-Zhou, 2012;Tahata et al, 2015;Sperling et al, 2015). This model, based on redox proxies, is consistent with petrographic evidence from the LCWI in South Australia, where primary dolomite cements in a reef complex with significant vertical relief record gradients in Fe and Mn , 2015.…”
Section: Palaeoenvironmental Evolutionsupporting
confidence: 60%
See 1 more Smart Citation
“…Available evidence suggests anoxic oceans (largely ferruginous but locally euxinic) beneath an oxygenated surface mixed layer (Och & Shields-Zhou, 2012;Tahata et al, 2015;Sperling et al, 2015). This model, based on redox proxies, is consistent with petrographic evidence from the LCWI in South Australia, where primary dolomite cements in a reef complex with significant vertical relief record gradients in Fe and Mn , 2015.…”
Section: Palaeoenvironmental Evolutionsupporting
confidence: 60%
“…Chronological and chemostratigraphic constraints on the mid-Cryogenian in general, although improving (Halverson et al, 2010;Rooney et al, 2014Rooney et al, , 2015, are currently more fluid than the base and top of the Cryogenian (Spence et al, 2016). A tuffaceous bed just above the Sturtian glaciation in South China has yielded a U-Pb age of 663 ± 4 Ma (Zhou et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Li et al . () argued from palaeomagnetic evidence, and entirely counter to the geological record, that Neoproterozoic glacially‐influenced deposits accumulated on ‘stable platforms’, others have suggested that globally‐correlative, orbitally‐forced ice advance and retreat cycles might ultimately be identified from such deposits (Condon et al ., ; Leather et al ., ; Arnaud, ; Rieu et al ., ; Hu et al ., ; Le Heron et al ., ; Benn et al ., ; Busfield & Le Heron, ; Spence et al ., ). These latter ideas are worthy of further investigation but need to be reconciled with what is known of the very active tectonic setting of many Neoproterozoic glacially‐influenced basin fills, which are overwhelmingly deep water mass flow dominated and rift‐related (Western North America, Greenland, Scotland and Scandinavia; Eyles & Januszczak, , ).…”
Section: Discussionmentioning
confidence: 99%
“…Most focus has been on the Sturtian ( ca 717–660 Ma) and the Marinoan ( ca 651–635 Ma) glaciations (Evans & Raub, ; Fairchild & Kennedy, ; Hoffman & Li, ; Hoffman et al., , ; Li et al., ; Rooney, Strauss, Brandon, & Macdonald, ; Zhao & Zheng, ; Zhou et al., ). Many workers consider these to be discrete global Snowball Earth glaciations, although poor global age control equally allows them to be viewed as diachronous (Spence, Le Heron, & Fairchild, ). Two other glaciations (Kaigas, ca 757–741 Ma, and Gaskiers, ca 590–582 Ma) are also recognized but considered to represent non‐Snowball Earth conditions (Gao et al., ; Li et al., ; Pu et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The Gaskiers glaciation of north east North America is an example of an increasingly tightly constrained glaciation, likely ≤340 Ka in duration, which was posited to have occurred <9.5 Myr prior to the advent of the Ediacaran biota (Pu et al., ). In spite of the emerging view that the Gaskiers glaciation is of regional, rather than global extent (Pu et al., ; Spence et al., ), glacial deposits of broadly similar age are recognized on other continents (Li et al., ). In China, these include the deposits of the Tarim Craton in the north‐west, and those of the North China Craton (NCC).…”
Section: Introductionmentioning
confidence: 99%